Fraud fighter : my fables and foibles - Wells, Joseph T. (Hoboken : John Wiley & Sons, 2011)
A collection of insightful, poignant, and humorous stories from Dr. Joseph Wells, the world's foremost fraud expert?with gutsy revelations of his own past mistakes. From his dysfunctional childhood in rural Oklahoma; his service in the U.S. Navy; a brief stint in public accounting followed by a career in the FBI; and founding the world's largest anti-fraud organization, Wells' colorful life experiences were preparation for his rise to one of the globe's most revered antifraud experts.:; Written by the preeminent antifraud authority and founder and Chairman of the ACFE; Offers a fascinating behi.
Machine generated contents note: Prologue. -- CHAPTER 1 My First White-Collar Crime Case: Age 28. -- The Early Years: To Age Six. -- At Sea, Off Scotland: 19 Years Old. -- My Dysfunctional Youth: Ages 6-12. -- Fred G. Robin, III: Age 29. -- Living on Less: Ages 12-14. -- Robin's Rump Roast Rip-Off: Age 30. -- Not a Fashion Maven: Ages 13-15. -- CHAPTER 2 Midland: Age 28. -- Being Dirt-Poor in the Land of Poor Dirt: Ages 14-16. -- A Gang of Thieves: Age 29. -- Looking Beyond High School: Ages 15-16. -- The Suicides: Age 29. -- High School: Age 16. -- Kevin "KevBomb" Flint: Age 33. -- Falling in Love the First Time: Age 16. -- Roger Corday: Age 34. -- Falling Apart in High School: Age 17. -- Saved by Bill, Margaret and Tina. -- The Best Looking Girl in High School: Age 17. -- Losing My Credentials: Age 32. -- CHAPTER 3 Off to the Navy: Age 17. -- Jim Warner: Age 36. -- I Left My Heart: Age 18. -- Ireland: Ages 19-21. -- Back to Oklahoma: Age 22. -- Fooling Around: Age 23. -- The Packrat: Age 41. -- The First Marriage: Age 24. -- Going to College: Age 24. -- CHAPTER 4 Something's wrong at the CIA: Age 38. -- The Evil Weed: Age 25. -- The Wonderful World of Auditing: Age 26. -- Becoming a G-Man: Age 27. -- The FBI Academy: Age 27. -- My Second Marriage: Age 28. -- Down in the West Texas of El Paso: Age 29. -- CHAPTER 5 New York: Age 30. -- The New York Office. -- Herman Simon Klegmeir: Age 30. -- Edgar M. Brodine, Jr.: Age 31. -- The Payoff. -- Thinking like an Accountant. -- Enter the Okie: Age 31. -- John N. Mitchell, Crooked Lawyer. -- Lies, Lies and Damn Lies. -- CHAPTER 6 Jackson, Here I Come!: Age 33. -- William G. Burgin, Jr.: Age 34. -- George S. Sewell, Jr. -- James Beauregard Turner. -- Sally Mulcasey. -- Laying a Trap. -- Roxanne Hurley. -- Sally vs. Roxanne. -- Finally, a Break. -- Mata Hari. -- Complicated Relationships. -- My Next Move. -- Learning Development Corporation. -- Digging for Dollars. -- Predication. -- Fred St. John. -- Lay Down, Sally. -- Follow the Money. -- A Fishing Expedition? -- Flavous Lambert. -- Goodbye, Roxanne. -- Confronting Burgin. -- Mulcasey and Sewell. -- The Grand Jury. -- Meeting Judy the First Time: Age 34. -- The Burgin-Lambert Trial: Age 35. -- CHAPTER 7 Austin and Beyond: Age 35. -- Meeting Judy the Second Time: Age 36. -- The Love of My Life. -- Branching Out: Age 37. -- Ending my FBI Career: Age 38. -- CHAPTER 8 Wells & Associates: Age 38. -- The Capitol Fire: Age 39. -- Meeting Jim Ratley: Age 39. -- Ross Perot: Age 40. -- Getting in to Crime Prevention Education: Age 42. -- Death Row: Age 43. -- CHAPTER 9 Money for Nothing: Age 43. -- Max Vance: Age 44. -- Meeting Mike Lawrence: Age 44. -- Working for a Living: Ages 38-45. -- Dr. Donald R. Cressey: Age 40. -- CHAPTER 10 In a Dream: Age 44. -- The Certified Fraud Examiner: Age 45. -- Dr. Gil Geis: Age 45. -- Seminars, Conferences and More Seminars. -- The CFE Exam. -- The American Association of Forensic Experts. -- More Litigation: Age 46. -- CHAPTER 11 Expanding the Common Body of Knowledge: Age 49. -- The "Boy Wonder": Age 50. -- Learning from Crooks. -- Fifteen Minutes of Fame. -- Still Growing: Age 52. -- Staying Put. -- Moving Sideways: Age 53. -- Starting Some Serious Fraud Research: Age 54. -- An International Presence: Age 55. -- CHAPTER 12 Me, My Addictions and Me: Ages 14-63. -- Fear of Flying: Age 38-55. -- Jim Ratley's Hobbies. -- Soloing Again: Age 62. -- Crashing but not Burning. -- Adrenaline Junkie. -- Starting in Higher Education: Ages 58-62. -- The Cliff Robertson Sentinel Award: Age 62. -- The Law Enforcement Partnership: Age 63. -- The Good Life: Age 65. -- Writing, Writing, Writing: Ages 55-65. -- The Future: Age 65 and Up. -- Postscript. -- Index.
Print version record.
John Wiley and Sons
Keywords: Wells, Joseph T; Wells, Joseph T; Fraud -- United States -- Case studies; Fraud investigation -- United States -- Case studies; Auditors -- United States -- Biography; Fraude -- v; z -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- General; LAW -- Forensic Science; Auditors; Fraud; Fraud investigation; United States; Biographies; Case studies